Topo-logical montages: the images on the capitals and pillars of the cloister of Moissac - Pereira, Maria Cristina Correia Leandro (Revista de História, 2011)
Based on George Didi-Huberman’s concept of “montage”, developed in his reading of Walter Benjamin and Aby Warburg, this article intends to refute the specialized bibliography on the cloister of Moissac that denies the existence of a logical order for its capitals. On the contrary, it will be demonstrated that this “place of images” is the result of several “topo-logical montages”.